2022
DOI: 10.1038/s41598-022-08266-1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of dental developmental anomalies among childhood cancer survivors according to types of anticancer treatment

Abstract: Survival following childhood cancer has increased considerably. In an observational cross-sectional study, we assessed the prevalence of dental developmental anomalies (DDA) among childhood cancer survivors according to types of anticancer treatment. Permanent teeth were examined clinically and radiographically in 121 adolescents with a history of childhood malignancies, to identify DDA, namely hypomineralization or hypoplasia, microdontia, root changes and hypodontia. DDA were observed in 56/121 individuals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 27 publications
1
21
1
4
Order By: Relevance
“…In contrast, the Norwegian study by Wilberg and coworkers (2016) on 111 survivors of childhood leukemia, treated with chemotherapy at an early age, hypodontia was found in 5%, microdontia in 28%, and enamel hypoplasia in 46% [9]. The higher prevalence of hypodontia in our study population compared to childhood leukemia survivors treated with chemotherapy [9] may be due to treatment modalities combining CSI with chemotherapy [40] in MB/CNS-PNET patients.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…In contrast, the Norwegian study by Wilberg and coworkers (2016) on 111 survivors of childhood leukemia, treated with chemotherapy at an early age, hypodontia was found in 5%, microdontia in 28%, and enamel hypoplasia in 46% [9]. The higher prevalence of hypodontia in our study population compared to childhood leukemia survivors treated with chemotherapy [9] may be due to treatment modalities combining CSI with chemotherapy [40] in MB/CNS-PNET patients.…”
Section: Discussioncontrasting
confidence: 82%
“…Several previous studies reported that vincristine and alkylating substances such as cyclophosphamide may be associated with DDD in childhood cancer survivors [6,11,41,42]. In contrast, in a recent published study no association between DDD and specific type of chemotherapy agent was reported [40]. Even though brain tumor patients are not directly irradiated towards the jaws and teeth, scattering to these surrounding tissues may occur [43].…”
Section: Discussionmentioning
confidence: 97%
“…Development disturbances can be influenced by genetic, epigenetics, and environmental factors, such as chemotherapy, radiotherapy, and chemoradiotherapy treatment at an early age. Various studies reported effects on craniofacial and dental development caused by chemotherapy administered during the stages of tooth development [ 4 , 6 , 10 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The subjective sensation of dry mouth is a potential side effect following head and neck radiation but the association of chemotherapy alone with xerostomia is controversial [ 12 ]. It can be concluded that the DMFT score (the sum of the number of Decayed, Missing due to caries, and Filled Teeth in the permanent teeth) of chemotherapy patients depends primarily on family history, hygiene patterns, and socioeconomic status [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…В работе было отмечено, что патология зубов чаще встречалась у больных, получавших лучевую терапию (53% случаев), в сравнении с выжившими, которые принимали только химиотерапию (43% случаев), ранний возраст пациента на момент начала лечения также повышал риск нарушения формирования зубов (p = 0,001). Статистически значимой связи между отдельными химиопрепаратами и патологией зубов не выявлено [47]. S.C. Kaste в 2009 г. представила результаты опроса и анализ влияния химио-и лучевой терапии, социально-экономических и демографических аспектов, возраста пациента на анатомию зубов [48].…”
Section: рисунокunclassified